Knowledge, Attitudes, and Perceptions of the Residents of the National Capital Region (NCR) towards Soil-Transmitted Helminthiasis and the Deworming Program of the Department of Health - Marquez, Charles Benedict; Joves, Sean Kyobi; Lantin, Niña Allysa Claire; Monte, Alyssa Mae; Torres, Jia Marie; Yeo, Mary Beatrice; Malana, Joemarie (International Journal of Arts, Sciences and Education, 2022)
Soil-transmitted helminthiasis (STH) is a parasitic infection affecting around 24% of the world’s population. These parasites are prevalent in vulnerable countries like the Philippines. Accordingly, the prevalence of STH continues to be high in certain areas in the country despite deworming programs in endemic areas. Hence, the study aimed to determine the knowledge, attitudes, and perceptions (KAP) of the residents of the National Capital Region (NCR) towards soil-transmitted helminthiasis and the deworming program of the Department of Health (DOH). Employing a quantitative, descriptive research design with the data gathered through online survey questionnaires among 211 NCR residents aged 18 to 59 years old, studies revealed that the respondents have a high level of knowledge (Bloom’s Cutoff Point=51.18%: High level=score of 23-28), positive level of attitude (x̄=91.15%), and neutral level of perception (x̄= 2.71: neutral=2.60-3.39) towards STH and the deworming program in which majority have access to this information through school education, information dissemination initiatives from DOH, and other data from the internet. Determining the relationships among the KAP, the results showed that only knowledge and general perceptions have a weak positive correlation (p=0.037). However, when the respondents are grouped into their sociodemographic profile, knowledge & occupation (p=0.020), attitudes with occupation & age (p=0.046; p=0.002), perceptions & age (p<0.001), and familiarity with the deworming program & sex (p<0.001) have shown significant relationships. The study raises awareness of the citizens’ knowledge, perspective, and attitudes wherein the government can improve their health sector and instill more emphasis on the deworming program. Overall, the respondents have satisfactory results regarding the KAP towards STH and the deworming program. Future researchers may consider doing a risk assessment to determine possible risk factors for STH infections.